2010
DOI: 10.1111/j.1601-5037.2009.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical study evaluating the long‐time adjunctive use of chlorhexidine after one‐stage full‐mouth SRP

Abstract: Over 3 months of extended use of CHX mouth rinse after SRP showed slightly but statistically significant better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Therefore, this systematic review aimed for the first time to evaluate the benefit of CHX after periodontal or implant surgery compared to rinsing with a placebo and second to discern the influence of different concentrations and formulations in terms of efficacy, side effects and patient acceptance. We hypothesized, as shown for gingivitis prophylaxis and non-surgical periodontal therapy [37,[38][39][40][41][42][43][44], that rinsing with CHX 1) Results in less plaque formation and bleeding as compared to placebo control 2) Novel formulations are able to reduce side effects while still being effective, i.e. are as effective in plaque and bleeding reduction as the respective control (standard CHX-formulation).…”
Section: Despite the Aforementioned Disadvantages Chemical Plaque Comentioning
confidence: 99%
“…Therefore, this systematic review aimed for the first time to evaluate the benefit of CHX after periodontal or implant surgery compared to rinsing with a placebo and second to discern the influence of different concentrations and formulations in terms of efficacy, side effects and patient acceptance. We hypothesized, as shown for gingivitis prophylaxis and non-surgical periodontal therapy [37,[38][39][40][41][42][43][44], that rinsing with CHX 1) Results in less plaque formation and bleeding as compared to placebo control 2) Novel formulations are able to reduce side effects while still being effective, i.e. are as effective in plaque and bleeding reduction as the respective control (standard CHX-formulation).…”
Section: Despite the Aforementioned Disadvantages Chemical Plaque Comentioning
confidence: 99%
“…Nevertheless, a prospective clinical study on patient undergoing one-stage full-mouth scaling and root planing has demonstrated a statistical significant benefit in probing depth and clinical attachment gain after 3 months of extensive use of CHX mouth rinse. [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the outcome of SRP antibiotics are used in severe forms of periodontitis [ 15 , 16 ] and mostly chlorhexidine rinsing is executed in the first days after SRP [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%